Plasmodium falciparum isolates from southern Ghana exhibit polymorphisms in the SERCA-type PfATPase6 though sensitive to artesunate in vitro - Kwansa-Bentum, B.; Ayi, I.; Suzuki, T.; Otchere, J.; Kumagai, T.; Anyan, W.K.; Osei, J.H.N.; Asahi, H.; Ofori, M.F.; Akao, N.; Wilson, M.D.; Boakye, D.A.; et al. (My University, 2011)
Abstract Background In 2005, Ghana replaced chloroquine with artemisinin-based combination therapy as the first-line treatment for uncomplicated malaria. The aim of this work was to determine for the first time, polymorphisms in the putative pfATPase6 and pftctp, pfmdr1, pfcrt genes in Ghanaian isolates, particularly at a time when there is no report on artemisinin resistance in malaria parasites from Ghana. The sensitivity of parasite isolates to anti-malaria drugs were also evaluated for a possible association with polymorphisms in these genes. Methods The prevalence of point mutations in the above Plasmodium falciparum genes were assessed from filter-paper blood blot samples by DNA sequencing. In vitro drug sensitivity test was carried out on some of the blood samples from volunteers visiting hospitals/clinics in southern Ghana using a modified version of the standard WHO Mark III micro-test. Results All successfully tested parasite isolates were sensitive to artesunate; while 19.4%, 29.0% and 51.6% were resistant to quinine, amodiaquine and chloroquine respectively. The geometric mean of IC50 value for artesunate was 0.73 nM (95% CI, 0.38-1.08), amodiaquine 30.69 nM (95% CI, 14.18-47.20) and chloroquine 58.73 nM (95% CI, 38.08-79.38). Twenty point mutations were observed in pfATPase6 gene, with no L263E and S769N. All mutations found were low in frequency, except D639G which was observed in about half of the isolates but was not associated with artesunate response (p = 0.42). The pftctp gene is highly conserved as no mutation was observed, while CVIET which is chloroquine-resistant genotype at codon 72-76 of the pfcrt gene was identified in about half of the isolates; this was consistent with chloroquine IC50 values (p = 0.001). Mutations were present in pfmdr1 gene but were not associated with artemisinin response (p = 1.00). Conclusion The pfATPase6 gene is highly polymorphic with D639G appearing to be fixed in Ghanaian isolates. These may just be spontaneous mutations as all parasite isolates that were tested displayed satisfactory in vitro response to artesunate. However, there is no improvement in susceptibility of the parasites to chloroquine five years after its proscription.